Long-term sorption and desorption of uranium in saprolite subsoil with nanoporous goethite. (March 2019) - Jung, Hun Bok; Xu, Huifang; Roden, Eric E.
Abstract: Long-term (2–3 months) batch U(VI) sorption-desorption experiments were conducted to understand the long-term sorption-desorption behavior of U(VI) in saprolite subsoils from Oak Ridge Field Research Center (ORFRC), Tennessee, which contained naturally occurring nanoporous goethite. Three subsoil samples containing a range of dithionite-citrate-bicarbonate (DCB) extractable Fe oxide content (7138, 11, 161, and 22, 582 mg Fe/kg) were used for the experiments. Sorption of 50 μM U(VI) to the subsoils in the presence of Ca 2+ and HCO3 − at circumneutral pH occurred rapidly during the first 2 days, after which slow U(VI) sorption continued over 3 months. U(VI) desorption from the soils by 10 mM NaHCO3 solution exhibited an initial fast desorption step during the first 24 h, followed by slower desorption over a week. Sorption of 50 μM U(VI) for 1 day to 3 months in the presence or absence of Ca 2+ consistently resulted in higher U(VI) sorption to saprolite soil with higher amount of nanoporous goethite, while desorption of U(VI) for 1 week to 2 months was consistently lower in saprolite soil with higher amount of nanoporous goethite. Saprolite subsoils containing higher amounts of nanoporous goethite exhibited more resistant U(VI) desorption, and the proportions of irreversible U(VI) sorption increased with longer residence time with soils. These results indicates that more U(VI) became bound to the internal surfaces of nanoporous iron oxides during long-term sorption. This study suggests that naturally occurring nanoporous goethite may exert a significant role in controlling the mobility and transport of U(VI) in historically contaminated sites that have existed over decades. Highlights: U(VI) sorption and desorption in saprolite soil occurred in multiple steps. U(VI) sorption to soil increased with higher amounts of nanoporous goethite. Soil with more nanoporous goethite showed more resistant U(VI) desorption. U(VI) sorption to soil became more irreversible with longer residence time. Long-term sorption resulted in more U(VI) bound to nanoporous surfaces.